SIMULATION AND ANALYSIS OF TIPOVER STABILITY OF WHEELED MOBILE MULTI-ROBOT COORDINATED TOWING SYSTEM - ZHANG ShaoHui; ZHAO ZhiGang; DING WangCai; SU Cheng (Jixie qiangdu)
In the process of mobile multi-robot coordinated towing,the mobile robot will cause a series of problems such as system damage,operation failure,and casualties due to its overturning. First,the system is divided into two parts: the mobile manipulator and the towing system. The kinematics models are established respectively. The Lagrangian method and the NewtonEuler method are used to establish the two parts of the dynamic model. The numerical method is used to solve the inverse kinematics of the system,and then to analyze the stability of the system based on the force-angle stability measure. Finally,Matlab software is used to compare the stability angles corresponding to the inverse kinematics of each group of manipulator to obtain a set of most excellent solution. The result lays the foundation for the further study of system motion stability,trajectory planning and system control.